Mengantarkan Seni Grafis Indonesia Menuju Pada Kematian - Mahendrapati, A. Nawangseto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2010)
Graphic arts (printmaking) is composing the image through the printing process with the purpose of reproduction or reproduce. History of graphic arts at first in Europe in the late 14th-century woodcut print used to make fabric patterns and print images for the following religious texts images-picture of a saint. Until the late 19th century graphic art has a role an informative function, as the dissemination of knowledge and as a medium of expression.The pioneers of graphic art in Indonesia is a visual artist,painter and sculptor,who found an alternative in the art print. Baharoedin M.S. and Mochtar Apin that makes a set of graphic works to be sent to countries that have recognized the sovereignty of Indonesia in 1946, is the painter. Momentum is regarded as heroic and patriotic moment that marked the birth of graphic arts in Indonesia.Talks abaout the art of graphic printing (printmaking) in Indonesia is always dwell on the issues concerning the position of inferiority issues in art map. Diversity techniques and material and assist in the creation of works of an artistic achievement of expression. But the opposite happened, as if the graphic arts lazy to move to find new things and seem like less sluggish blood.The development of graphic art certainly does not escape the role arts education institutions because, in general the new graphic art can be studied in educational institutions because of the workmanship is in need of facilities such as a studio representative and supported by the equipment that had to be there. Beyond that not a lot of agencies or organizations that facilitate or support the activities of the graphic arts. Therefore it is necessary to form a powerful synergy of inter-related infrastructure and support every movement printmaking Indonesia and able to spur a more lively movement or at least make an effort to slow death.Keyword : graphic arts, lethargy, effort, synergy